Exposing social constructions in Vonnegut’s Cat’s Cradle through metareligion - Babaei, Abdolrazagh; Wan Yahya, Wan Roselezam (Universiti Putra Malaysia Press, 2013)
Bokononism is a fictional religion Vonnegut brings into his narrative, Cat’s Cradle (1963), to create a self-conscious novel known as metafiction. This innovative mode of writing narratives, along with providing a critique of their own methods of construction, deals with the external real world to examine some established structures of the human society like religion. By exposing the fundamental structures of narrative fiction, Vonnegut’s novel gives readers an opportunity to think about the possible fictionality of the world structures outside the literary fictional text. The novel tries to reorder the world perception of readers through rearranging the values and conventions of the fiction he produced. Vonnegut’s fourth novel, Cat’s Cradle, is the first mature work which, in its use of metafiction, presents ideas about the nature of truth, dealing as it does with science and religion as its main topics. A novel telling the story of its writing shifts its metafictional focus on writing process to social concern of the novelist by means of those very metafictional strategies. What the study refers to as metareligion is an ideological product of metafictional writing which Vonnegut introduces in his novel. The same as metafiction that “self-consciously and systematically draws attention to its status as an artefact”, Vonnegut’s metareligion exposes the metaphor of its own duplicity and simulacrum not pretend any longer to pass for the reality of what human being keep as a sacred religion. As a metafictional novel, Cat’s Cradle aims at leading readers to question whether the world systems in general and religion in particular could be as constructed as the novels they are reading.